Blockchain Dispute Resolution for Decentralized Autonomous Organizations: The Rise of Decentralized Autonomous Justice - Guillaume, Florence; Riva, Sven (Leiden / Boston: Brill Nijhoff, 2023)
For the past twenty years, the use of the Internet has facilitated international commercial relations between people who do not know each other and who are geographically distant. Disputes resulting from e-commerce have undermined the supremacy of state courts, which have proved unable to provide an appropriate response to small claims arising in an international context and raising delicate questions as to jurisdiction and applicable law. The length, cost and complexity of the procedure, as well as the risk associated with the international enforcement of the judgment are deterrent factors that led e-commerce platforms to develop online dispute resolution (ODR). Thanks in part to the removal of intermediaries, the transfer of cryptocurrencies and other crypto assets using blockchain technology has further facilitated international commercial relations. The decentralized and distributed characteristics of blockchain technology and the pseudonymity of its transactions has led to a new economy growing independently from nation states. This technology has brought an additional degree of complication in the application of private international law (PIL) rules by removing the illusion that online transactions can be linked to the territory of a state. Smart contracts also allow the creation of digital entities that can enter into commercial relations. The first decentralized autonomous organization (DAO) was the source of a resounding dispute between parties with diverging interests, which had to be urgently resolved without any access to state courts or a dispute resolution mechanism. This case revealed the risk of disputes in the blockchain environment and the resulting legal uncertainty, and led to the emergence of various models of blockchain dispute resolution (BDR) mechanisms (BDRs) inspired by the solutions developed in e-commerce. This chapter deals with the application of PIL rules to the resolution of disputes involving DAOs. The authors first analyze what is a DAO and whether DAOs legally qualify as companies. What is at stake is the legal personality of DAOs and their capacity to conduct legal proceedings. The authors then examine whether disputes involving DAOs may be brought before state courts. This analysis highlights the problems related to the location, pseudonymity, and uncertainty regarding the legal personality of the participants of the blockchain environment, which challenge the jurisdiction of state courts in case of a dispute. The authors then draw on the experience acquired in the field of e-commerce to examine the advisability of setting up alternative dispute resolution mechanisms available to the actors of the blockchain environment. Based on an analysis of existing BDRs, the authors examine whether and how BDRs are likely to avoid a denial of justice and bring legal certainty to disputes related to contractual relationships with DAOs formalized through smart contracts as well as disputes related to the governance of DAOs. The authors find that a BDR decision which can be directly enforced through smart contracts confers effective justice to the actors of the blockchain environment. Finally, the authors address the more delicate issue of the enforcement of a BDR decision on non-crypto assets. This approach shows that a type of justice based on cryptoeconomic incentives challenges the concept of fair justice. This could be an impediment to obtaining the assistance of state authorities for the enforcement of a BDR decision outside of the blockchain environment as this type of decision could be considered contrary to public policy. The analysis is mostly based on Swiss private international law and major private international law conventions. In this chapter, the authors outline the contours of a new private justice system designed to provide decentralized autonomous justice to the actors of the crypto economy.
Keywords: Decentralized autonomous organization; DAO; Decentralized finance; DeFi; Smart contract; Dispute resolution; Access to justice; Jurisdiction; Online dispute resolution; ODR; Blockchain dispute resolution; Crypto economy; Governance; Justice; Recognition and enforcement of decisions; Droit international privé; Blockchain; LegalTech; Cryptomonnaie